Asymmetric competitive effects during species range expansion: An experimental assessment of interaction strength between "equivalent" grazer species in their range overlap. Issue 2 (2nd November 2018) - Aguilera, Moisés A.; Valdivia, Nelson; Jenkins, Stuart; Navarrete, Sergio A.; Broitman, Bernardo
Abstract: Biotic interactions are central to the development of theory and concepts in community ecology; experimental evidence has shown their strong effects on patterns of population and community organization and dynamics over local spatial scales. The role of competition in determining range limits and preventing invasions at biogeographic scales is more controversial, partly because of the complexity of processes involved in species colonization of novel habitats and the difficulties in performing appropriate manipulations and controls. We examined experimentally whether competition is likely to affect poleward range expansion hindering or facilitating the establishment of the limpet Scurria viridula along the south‐eastern Pacific rocky shore (30°S, Chile) in the region occupied by the congeneric S. zebrina . We also assessed whether competition with the "invader" or range‐expanding species could reduce individual performance of the "native" S. zebrina and depress local populations Geographic field surveys were conducted to characterize the abundance and identity of limpets along the south‐eastern Pacific coast from 18°S to 41°S, and the micro‐scale (few cm) spatial distribution across the range overlap of the two species. Field‐based competition experiments were conducted at the southern leading edge of the range of S. viridula (33°S) and at the northern limit of S. zebrina (30°S). Field surveys showed poleward range expansion of S. viridula of ca. 210 km since year 2000, with an expansion rate of 13.1 km/year. No range shift was detected for S. zebrina . The resident S. zebrina had significant negative effects on the growth rate of the invading juvenile S. viridula, while no effect of the latter was found on S. zebrina . Spatial segregation between species was found at the scale of cms. Our results provide novel evidence of an asymmetric competitive effect of a resident species on an invader, which may hamper further range expansion. No negative effect of the invader on the resident species was detected. This study highlights the complexities of evaluating the role of species interactions in setting range limits of species, but showed how interspecific competition might slow the advance of an invader by reducing individual performance and overall population size at the advancing front. Abstract : The authors' results provide novel evidence of an asymmetric competitive effect of a resident species on an invader, which may hamper further range expansion. Thus, showing how interspecific competition might slow the advance of an invader by reducing individual performance and overall population size at the advancing fronts.